Proposal to Reclassify SCCPs Under International Regulations on Ship Recycling to Enhance Environmental and Human Health Protection - Jelena Čulin (Applied Sciences)
Short-chain chlorinated paraffins (SCCPs) are ubiquitous environmental pollutants that have been detected in various human tissues and organs. Based on the results of numerous studies indicating that exposure to environmentally relevant doses could induce harm to humans and animals, they have been listed in Annex A (Elimination) of the Stockholm Convention on Persistent Organic Pollutants. They are also listed as hazardous materials likely to lead to significant adverse effects on human health or the environment by the International Convention for the Safe and Environmentally Sound Recycling of Ships (Hong Kong Convention) and the EU Ship Recycling Regulation (EU SRR). This paper analyzes recent literature on the environmental and human health impacts of SCCPs and the actual practice of shipbreaking to demonstrate that the current treatment of SCCPs under these two regulations does not provide sufficient protection for human health and the environment. Based on the presented data, it is proposed that SCCPs should be reclassified as materials whose installation or use is prohibited in shipyards, ship repair yards, and ships by the EU SRR and the Hong Kong Convention.